De procesiones y cosinages: fiestas y convites en el marco de las cofradías religiosas de indios en Potosí (Alto Perú) durante el período colonial = Of processions and cosinages : parties and treats within the framework of the religious brotherhoods of Indians in Potosí (Alto Peru) during the colonial period - De Luca, María Candela (Ciencias sociales y religión, 2014)
Considering that colonial festivities -that in the whole Upper Peru presented religious features-are a strategic space whereto detect the reproduction and expression of cultural values, in this paper we aim to observe and describe religious festivities that existed in Potosí during the XVIIIth century. The religious ceremonies developed in the framework of those institutions favoredthe linkages between different actors in a society where religion was the axis of daily life. Without neglecting the religious nature of such festivities, it must be taken into account that they were the scenario of significant economic and political activities -since, for example, local elections were held there-. In this spirit, we will go through the sources describing such events, aiming to understand the different contents that reflected these practices, presenting both an explicit and symbolic nature.